1983
DOI: 10.1007/bf00257339
|View full text |Cite
|
Sign up to set email alerts
|

Coincident presence of thyro-gastric autoimmunity at onset of Type 1 (insulin-dependent) diabetes

Abstract: Summary.We have determined thyroid microsomal and gastric parietal cell autoantibodies in 972 patients with onset of Type 1 (insulin-dependent) diabetes before age 20 years. In a cross sectional study, the frequencies of these autoantibodies did not change significantly over the ensuing 20 years following diagnosis of diabetes. In a longitudinal study of 424 patients with Type 1 diabetes followed up to 5.3 years, few new patients with thyro-gastric autoantibodies were identified. Whereas the frequencies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…The prevalence of TMA among Type 2 diabetic patients was not significantly higher than in their non-diabetic counterparts. Riley et al reported that the frequency of TMA shows a major increase after the fifth decade of life [10]. The diabetic patients in this study were significantly older than the control subjects; despite that, they did not have a significantly higher frequency of TMA.…”
Section: Discussioncontrasting
confidence: 49%
“…The prevalence of TMA among Type 2 diabetic patients was not significantly higher than in their non-diabetic counterparts. Riley et al reported that the frequency of TMA shows a major increase after the fifth decade of life [10]. The diabetic patients in this study were significantly older than the control subjects; despite that, they did not have a significantly higher frequency of TMA.…”
Section: Discussioncontrasting
confidence: 49%
“…This prevalence of ICA was slightly higher than reported in other studies on Caucasian and Japanese patients (37)(38)(39). This increased positivity percentage could be explained by use of a more sensitive assay and also perhaps by the time chosen for screening: the subjects were all sampled at the time hyperthyroidism was diagnosed, when autoimmunity phenomena were not only active, but perhaps enhanced (40).…”
Section: Discussionmentioning
confidence: 51%
“…In a previous study, however, we found by both cross-sectional and longitudinal observations of children with IDDM that in the large majority of cases thyroid and gastric autoantibodies had usually appeared by the time of onset of IDDM, with few patients developing these antibodies at a later time. 16 In an expanded cross-sectional series of the patients (Table 1), modest and nonsignificant increases in the frequencies of these autoantibodies could be seen as the follow-up period was extended beyond 10 yr after diagnosis of IDDM (Figure 2), especially in the female patients. Whereas such a late increase of frequencies of thyroid and gastric autoantibodies in patients with IDDM may reflect the trend of the general population as a whole, it is possible that in most cases autoimmune disorders involving pancreatic islets and thyroid and gastric mucosa occur simultaneously, albeit these diseases have different natural histories.…”
Section: Effect Of Age Of Onset and Duration Of Iddm On Occurrence Ofmentioning
confidence: 92%